Asset Management, Pt Taisho Pharmaceutical Tbk - Wiratama, Aldi; Muktiadji, Nusa; Cahyani, Nani (LPPM Institut Bisnis dan Informatika Kesatuan, 2019)
Assets are important aspects of a company. Many firms still consider physical assets management as a tool or instrument in assets list management. The reality reveals that many cases initially started off from assets mismanagement, and eventually cause great loss to the company. Assets management is a process of wealth management both tangible and intangible ones, that are expected to have economic values and aimed at gaining profit and reduce costs efficiently and effectively. An appropriate assets management improves financial performance and increases revenues from assets utilization and reduces maintenance costs. The study aims at identifying how the financial performance and assets management in PT Taisho Pharmaceutical, Tbk. seen from its financial ratios and how its financial performance compared to industrial average financial performance of pharmaceutical sub sector. The financial reports used in this study are obtained from idx.co.id for the periods of 2012-2016. Analytical methods used are trend analysis, operating cycle, and financial ratio analysis. Based on the analysis, it can be concluded that assets management of PT Taisho Pharmaceutical generally fall into good category. This can be viewed from the activity ratios (TATO, CATO, FATO, INTO, ARTO) which are visibly increasing. Nonetheless, the company could not afford to optimize the efficiency of cost of goods sold and operating cost, and it has caused a less maximum gain in profits. The percentage of cost of goods sold and operating costs are larger than the sales percentage. The large amount of cost of goods sold is due to company’s policy granting employees extra training to produce more innovation for new products, and the increasing operating costs occurred owing to company’s increaseing sales volumes which resulted in additional costs for packing, delivery, and electrical engines. There are still some major improvements to make, considering some of the financial ratios are still under the average industrial score for pharmaceutical sub sector. The improvement of financial performance is necessary to push the profit gains and advancing the stakeholders wellfare.